Tax Effort, Flypaper Dynamics, and Fiscal Stress: An Empirical Study of Regional Financial Independence - Alazhari, Mutiara Andika; Hendaris, Raden Budi (E-Jurnal Akuntansi, 2025)
Regional financial independence reflects the success of implementing regional autonomy. However, the disparity in the level of independence between regions is still quite high, and many regions have not been able to implement autonomy effectively. This study aims to obtain clearer empirical evidence regarding the effect of Tax Effort, the Flypaper Effect, and Fiscal Stress on Region’s Level of Financial Independence. The data used are secondary data obtained from the APBD Realization Reports and GRDP, sourced from djpk.kemenkeu.go.id and bps.go.id for 2019–2023. The population in this study was determined using a census technique, covering 18 regencies and 9 cities in West Java Province. Data analysis is done using SPSS 27 software and multiple linear regression. This study's results demonstrate that Tax Effort has significantly positive effect on the level of regional financial independence. The Flypaper Effect has a significant negative effect on the Level of Regional Financial Independence. Fiscal Stress does not have significant effect on the level of Regional Financial Independence. Keywords: Tax Effort; Flypaper Effect; Fiscal Stress; Level of Regional Financial Independence.